The still of night - Heitzmann, Kristen (Bethany House, 2003)
Known professionally as the "success guru," Morgan Spencer is the turn- around genius who revitalizes failing corporations, and his gifts for identifying problems and finding solutions extends to the personal lives of his friends and acquaintances, but the one life he can't seem to set straight is his own: behind his charming rebel facade is a need that drives him toward success- and emptiness.